Empowering Conceptual Mastery and Learning Autonomy through Canva-Assisted Problem-Based Learning Worksheets - Meka, Ike Yunia; Sukasih, Sri; Aeni, Kurotul (Mimbar Ilmu, 2024)
The problem underlying this research is the low mastery of concepts and the lack of learning independence of students in the learning process. This research aims to develop Student Worksheets (LKPD) assisted by Canva using the Problem Based Learning (PBL) model to increase students’ mastery of concepts and learning independence. This research uses a Research and Development (R&D) approach with seven simplified steps, including needs analysis, product design, expert validation, revision, field trials, final product revision, and dissemination. Data collection was carried out through expert validation questionnaires, learning outcomes tests, learning independence questionnaires, and student response questionnaires. Data was analyzed descriptively, quantitatively and qualitatively. The product trial involved 21 students from an elementary school. The research results show that the LKPD assisted by Canva that was developed is valid and suitable for use based on expert assessments. The N-Gain value obtained shows an increase in concept mastery. In conclusion, Canva-assisted LKPD with the PBL model is effective in increasing students’ mastery of concepts and learning independence, making it suitable for use as an innovative learning medium in elementary schools. Implications of this research shows that the use of digital technology in learning can increase student engagement and understanding of the concepts being studied.